Hubungan antara Mikrobiota dan Psoriasis - Alinta Ayuningtyas Alinta; Khairun Nisa Berawi; Nurul Islamy (Jurnal Ilmu Medis Indonesia, 2021)
As the largest organ of the human body, the skin is colonized by a variety of microorganisms, most of which are harmless and have benefits for the host. This microbiota contributes to the metabolism and immunity of the host. The human microbiota includes bacteria, fungi, viruses and archaea, which inhabit various areas of the body. Most of the microbiota resides in the intestine, only a small part of which inhabit epithelial surfaces such as the mouth, airways, vagina and skin. The total number of microbiota on the surface of the skin is usually in the range 104 to 106 cells per cm2. Psoriasis is one of the most common immune-mediated inflammatory skin diseases. The prevalence of disease has been reported, with a range of 0.09- 11.43% by the WHO Global Report 2016. To date the causes of this disease are not fully understood, genetic and environmental interactions play an important role in disease progression. Recently, immunological approaches have helped to clarify the pathophysiology of the disease significantly. The skin microbiota has been shown to play a role in the pathogenesis of lichenified plaque formation in psoriasis. Corynebacterium, Propionibacterium, Staphylococcus, and also Streptococcus have been identified as the main microbiota. It has not been determined whether these changes in the microbiota are a cause or consequence of psoriasis. For this reason, further research on selective modulation of the skin microbiota is needed. This systematic review aims to elucidate the correlation between the microbiome and pathogenesis of psoriasis and the modulation of the microbiota that could lead to possible therapeutic interventions. Keywords: Microbiota, Psoriasis, Skin